PENERAPAN PRINSIP-PRINSIP INTERNATIONAL CONVENTION ON TRAVEL CONTRACTS DALAM TRANSAKSI JASA PERJALANAN WISATA - Irma Prawita Saragih; Ida Bagus Wyasa Putra; Made Suksma Prijandhini Devi Salain (Kertha Negara : Journal Ilmu Hukum, 2014)
travel) between the members agent or travel services (travel) is subject to the provisions ofcontract law in Indonesia and in particular, it is also regulated under the InternationalConvention Travel Contract. In fact, not all travel service agency contracts in Denpasar-Balirefer to the provisions of the convention in concern. It shows that the contract lacked thecapacity to prevent disputes, control of potential disputes, and resolve issues arising from acontract that has been made